2023
DOI: 10.1111/psyp.14500
|View full text |Cite
|
Sign up to set email alerts
|

Robust single‐trial event‐related potentials differentiate between distress and fear disorders

Martin Randau,
Nina Reinholt,
Cyril Pernet
et al.

Abstract: Recent evidence indicates that measures of brain functioning as indexed by event‐related potentials (ERPs) on the electroencephalogram align more closely to transdiagnostic measures of psychopathology than to categorical taxonomies. The Hierarchical Taxonomy of Psychopathology (HiTOP) is a transdiagnostic, dimensional framework aiming to solve issues of comorbidity, symptom heterogeneity, and arbitrary diagnostic boundaries. Based on shared features, the emotional disorders are allocated into subfactors Distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 141 publications
0
2
1
Order By: Relevance
“…At first sight, this conclusion contradicts the results from our previous study, where the Distress patients with a primary ICD-10 diagnosis of depression and GAD-had a significantly reduced CRN compared to healthy comparison subjects (Randau et al, 2023). However, group-level differences between HiTOP subfactors based on primary ICD-10 diagnosis do not necessarily translate to correlations with transdiagnostic symptomatology.…”
Section: Crncontrasting
confidence: 91%
See 2 more Smart Citations
“…At first sight, this conclusion contradicts the results from our previous study, where the Distress patients with a primary ICD-10 diagnosis of depression and GAD-had a significantly reduced CRN compared to healthy comparison subjects (Randau et al, 2023). However, group-level differences between HiTOP subfactors based on primary ICD-10 diagnosis do not necessarily translate to correlations with transdiagnostic symptomatology.…”
Section: Crncontrasting
confidence: 91%
“…In that study, the patient group had a significantly increased ERN compared to the healthy comparison group. For our present sample, we have recently shown that a subsample based on the HiTOP subfactor Distress-containing the ICD-10 diagnoses of Depression and GAD-had a reduced ERN at baseline compared to healthy comparison subjects (Randau et al, 2023). In that study, the ERN of the Fear subfactor-containing agoraphobia, OCD, PD, and SADwas not significantly different to either the Distress or HC group.…”
Section: (See Below)mentioning
confidence: 39%
See 1 more Smart Citation